Housing Density and Ecosystem Function: Comparing the Impacts of Rural, Exurban, and Suburban Densities on Fire Hazard, Water Availability, and House and Road Distance Effects - Jelena Vukomanovic; Sandra L. Doumas; W. R. Osterkamp; Barron J. Orr (Land, 2013)
Many amenity-rich regions are experiencing rapid land-use change through low-density residential development or exurbanization. Those same natural-resource amenities that attracted migration are often degraded by housing growth and associated development. This study examines the impacts of exurbanization on three ecosystem indicators (fire hazard, water availability, and generalized distance effects of houses and roads) and compares them to areas with rural and suburban housing densities in the Sonoita Plain, southeastern Arizona. We found that although they support significantly lower population densities, exurban areas have impacts on ecosystem function comparable to suburban areas. Exurban areas had the highest potential for fire, suggesting that it is the presence of people rather than the density that increases fire hazard. The increase in the number of wells in exurban areas far exceeded suburban areas and matched increases for agricultural use in rural areas. When the impacts of houses and roads on ecosystem function were considered, 98% of exurban areas were “highly” or “very highly” impacted, compared to 100% for suburban areas and 35% for rural areas. Since development in the area is not readily visible, assessing the spatial extent of impacts is important for understanding the vulnerability of systems and guiding decisions about development.